2013
DOI: 10.1103/physrevd.88.073002
|View full text |Cite
|
Sign up to set email alerts
|

Neutronβdecay as a laboratory for testing the standard model

Abstract: We analyse the sensitivity of all experimentally observable asymmetries and energy distributions for the neutron β − -decay with a polarized neutron and unpolarised decay proton and electron and the lifetime of the neutron to contributions of order 10 −4 of interactions beyond the Standard model (SM). Since the asymmetries and energy distributions are expressed in terms of the correlation coefficients of the neutron β − -decay, in order to obtain a theoretical background for the analysis of contributions beyon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
307
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(320 citation statements)
references
References 111 publications
12
307
0
Order By: Relevance
“…The authors showed that the account for the contributions of the proton photon correlations in the radiative corrections to the neutron beta decay does not contradict the description of the radiative corrections to the lifetime of the neutron and the proton recoil spectrum in terms of the standard radiative corrections but makes the proton recoil asymmetry C symmetric with respect to change of correlation coefficients A -B. They showed that the Standard Model describes well the lifetime of the neutron τ = 880.1(1.1)s with the theoretical value τ = 879.6(1.1)s, for the axial coupling constant ratio λ = −1.2750(9) and CKM matrix elements V ud obtained from the 0 + → 0 + transitions and the unitarity condition, respectively [30].…”
Section: Theoretical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors showed that the account for the contributions of the proton photon correlations in the radiative corrections to the neutron beta decay does not contradict the description of the radiative corrections to the lifetime of the neutron and the proton recoil spectrum in terms of the standard radiative corrections but makes the proton recoil asymmetry C symmetric with respect to change of correlation coefficients A -B. They showed that the Standard Model describes well the lifetime of the neutron τ = 880.1(1.1)s with the theoretical value τ = 879.6(1.1)s, for the axial coupling constant ratio λ = −1.2750(9) and CKM matrix elements V ud obtained from the 0 + → 0 + transitions and the unitarity condition, respectively [30].…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…This was done in [30] within the standard quantum field theory at the rest frame of the neutron and in the non-relativistic approximation for the proton by taking into account the radiative corrections to order alpha, the proton recoil correction and the weak magnetism to order 1/M, where M is the average mass [31]. The authors showed that the account for the contributions of the proton photon correlations in the radiative corrections to the neutron beta decay does not contradict the description of the radiative corrections to the lifetime of the neutron and the proton recoil spectrum in terms of the standard radiative corrections but makes the proton recoil asymmetry C symmetric with respect to change of correlation coefficients A -B.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…We note, however, that our limits are comparable to those obtained from fits to the entire beta decay set when similar assumptions are made (no right-handed neutrinos). This brief report was inspired by comments in Bhattacharya et al [3] and begun as a part of thesis research [4]; however, we note that additional details have subsequently been published by Ivanov, Pitschmann, and Troitskaya [5].…”
Section: Introductionmentioning
confidence: 99%
“…Not least, new physics searches with 10 −4 sensitivity need adequate input from theory: the existing analysis of correlation coefficients a, A, B, C, and D [134] must be extended to order 10 −5 , and completed with non-standard correlation coefficients G, N, Q, R [135], and L to order 10 −3 .…”
Section: Theoretical Considerationsmentioning
confidence: 99%